A Brief Analysis of Gravitational Search Algorithm (GSA) Publication from 2009 to May 2013 - Tengku Ibrahim, Tengku Nadzion; Thiyagarajan, Marapan; Hasim, Saipol Hadi; Zainal Abidin, Amar Faiz; Omar, Norhaizat; Nordin, Nur Anis; Jaafar, Hazriq Izzuan; Khairuddin, Osman; Ab Ghani, Zailani; Mohd Hussein, Shamsul Faisal (2014)
Gravitational Search Algorithm was introduced in year 2009. Since its introduction, the academic community shows a great interest on this algorith. This can be seen by the high number of publications with a short span of time. This paper analyses the publication trend of Gravitational Search Algorithm since its introduction until May 2013. The objective of this paper is to give exposure to reader the publication trend in the area of Gravitational Search Algorithm.